Heterosis for yield and physio-biochemical traits in bread wheat (Triticum aestivum L.) under different environmental conditions (Bangladesh Journal of Botany, 2020)
The heterosis study for grain yield and yield attributes was carried out in bread wheat (Triticum aestivum L.) through half diallel mating design in four environments. The pooled analysis of variance revealed significant differences between the environments for all the characters, indicating that environments had significant effect on the expression of different characters. The variance due to parents and F1 was also significant for all the characters, indicating significant difference between parents and hybrids and average heterosis was there. The magnitude of heterobeltiosis and standard heterosis altered for all the crosses and for all the characters. For the traits viz., total protein content, chlorophyll content, proline content, chlorophyll stability index and grain yield per plant quite a large number of crosses manifested positive significant heterosis over the checks. The hybrids HI 1544 × HD 2987, Raj 4037 × HD 2987, PBW 175 × HD 2987, HD 2932 × Raj 4079 and PBW 175 × Lok 1 exhibited the highest, significant and positive heterotic effect and mean performance for grain yield per plant and some of its important component traits. This could be exploited commercially for heterosis breeding in wheat.